PENGENALAN KARAKTERISTIK DAGING SEBAGAI SUMBER PROTEIN HEWANI (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Meat is a food of animal origin (PAH) which is in great demand by the public as a source of protein which contains essential amino acids to meet the body's needs. The availability of meat and needs is not balanced, coupled with the fairly high price of beef on the market, this has caused some individuals to abuse it by adulterating meat. The method used in this community service is socialization and demonstration of the introduction of the characteristics of meat from several livestock animals. The results achieved in this service are increasing participants' knowledge regarding the characteristics and characteristics of livestock meat, thereby minimizing the occurrence of meat adulteration and handling meat properly and correctly. The service activity involved lecturers from the Faculty of Animal Husbandry, Wijayakusuma University and was carried out well at the Banyumas Regency Satpol PP Office.